Alternative substrates for production of yellow passion fruit seedlings - Aires, Eduardo Santana [UNESP]; Aragao, Carlos Alberto; Silva Gomes, Itala Laiane; Souza, Gilmario Noberto de; Vieira de Andrade, Isa Gabriela (Univ Estadual Mato Grosso Sul, 2020)
This study aimed to evaluate different substrates to produce yellow passion fruit seedlings. For this purpose, an experiment was carried out in a greenhouse, from April to June 2016. A completely randomized design with five replications, in a 6 x 5 factorial scheme was used. The first factor was the alternative substrates (poultry, cattle and equine manure, sugarcane and coconut bagasse, and Organomais compost). The second factor was the replacement levels to the commercial substrate of Plantmax (R) (100:0, 75:25, 50:50, 25:75, 0:100). The seedling evaluation was carried out 42 days after sowing. The following variables were analyzed: length, width, and the number of leaves; plant height and shoot dry matter. A significant effect (P<0.05) for the interaction between the factors was verified. The addition of 60% cattle manure and Organomais to the commercial substrate Plantmax (R) promoted greater length, width, and the number of leaves, plant height, and shoot dry matter accumulation in the yellow passion fruit seedlings.
Keywords: initial plant growth; organic matter; Passiflora edulis Sims f. flavicarpa Deg